The Principal’s Strategy in Improving the Noble Character of Children with Special Needs at SLB Tamima Mumtaz - Imam Syuhro Wardi (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the principal’s strategies in improving the noble character of students at SLB Tamima Mumtaz. This research uses a qualitative approach with a case study type to obtain in-depth and comprehensive data. Data collection techniques were carried out through observation, in-depth interviews, and documentation relevant to the research focus.The results of the study indicate that the principal has a strategic role in shaping character through various religious programs and positive habituation. In conclusion, well-planned and collaborative strategies are able to effectively improve the noble character of students.